2018
DOI: 10.1108/jmtm-09-2017-0194
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain performance: how lean practices efficiently drive improvements

Abstract: Purpose The purpose of this paper aims at investigating which lean supply chain management (LSCM) practices efficiently improve the supply chain performance. Design/methodology/approach To achieve that, a cross-sectional survey was carried out with 113 manufacturing companies undergoing a lean implementation. The proposed method combines complementary methods of multivariate data analysis in order to determine which bundles of LSCM practices more efficiently entail improvements on supply chain performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 74 publications
1
28
0
Order By: Relevance
“…Qi et al (2011) found that LSCM is more effective at improving business performance in a stable environment. Recently, Tortorella et al (2018) found that LSCM practices related to customer-supplier relationship management (CSRM) indicate contradictory findings on delivery, costs and lead time.…”
Section: Lean Supply Chain Management-focal Firm Efficiency Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Qi et al (2011) found that LSCM is more effective at improving business performance in a stable environment. Recently, Tortorella et al (2018) found that LSCM practices related to customer-supplier relationship management (CSRM) indicate contradictory findings on delivery, costs and lead time.…”
Section: Lean Supply Chain Management-focal Firm Efficiency Relationshipmentioning
confidence: 99%
“…At the external level, the literature analyses the impact on operating results of LM practices along the SC such as waiting time, inventory rotation and on time delivery, also with mixed results (e.g. McIvor, 2001;Tortorella et al, 2018). It would, therefore, be interesting to use an integrated focus on LSCM and to examine the impact on other types of operating results, such as efficiency, which Shah and Ward (2003) state is one of the results that LM mostly impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Some Lean Production practices are implemented with ease in the supply chain providing flexibility (e.g. continuous improvement, waste reduction, teamwork, suppliers management and 5S) which allows to respond to variations in demand (Moyano-Fuentes et al, 2012a;Stump and Badurdeen, 2012;Singh and Teng, 2016;Tortorella et al, 2018). Lean Production enables grouping basic elements of product family members into a common module, which would be used to derive different product variants and combine them with different components (Moyano-Fuentes et al, 2012a).…”
Section: Lean Production Implementation and Supply Chain Flexibilitymentioning
confidence: 99%
“…Moyano-Fuentes et al (2020) found that there is an improvement in the efficiency of the focal firm when lean management extends throughout the supply chain. Lean implementation has a significant positive impact on business performance by acting on the causes of waste and inflexibility, improving production efficiency, removing process redundancies and cutting production costs (Novais et al , 2020; Tortorella et al , 2018a, 2018b; DeGroote and Marx, 2013; Stump and Badurdeen, 2012; Hopp and Spearman, 2004).…”
Section: Measures To Improve Supply Chain Efficiencymentioning
confidence: 99%